Identifikasi Manfaat Bagi Anggota Pada Koperasi Produsen Peternakan Sapi Perah - Roja Hasanah, Fatiya; Sugiyanto, Sugiyanto (Universitas Koperasi Indonesia, 2024)
Cooperatives as business entities are actually formed with the intention of being able to provide welfare, especially for members and generally for the community. The realization of the intended welfare is in the form of benefits that can be felt so that in the long run it can improve the community's economy. One type of cooperative that is increasingly present in the lives of community farmers is a dairy farm producer cooperative. In its operational activities, members as farmers play a role in producing dairy milk which is then deposited with the cooperative at a purchase price that is relatively dependent on the quality of dairy milk, then to be processed until the marketing stage to the Milk Processing Industry with a predetermined selling price. This is one of the price benefits received by members, as well as good facilities and services that are able to meet the needs of members. The method used in this research is a qualitative approach, with the type of research method, namely comparative descriptive qualitative method with case studies on cooperatives in West Bandung Regency. This method is carried out to identify the benefits for members in dairy farm producer cooperatives and solutions for cooperatives to increase and or increase benefits for their members.